2009
DOI: 10.1183/09031936.00167608
|View full text |Cite
|
Sign up to set email alerts
|

Second-hand smoke exposure in cars and respiratory health effects in children

Abstract: We examined potential associations of ever asthma, and symptoms of wheeze (past 12 months), hay fever, eczema and bronchitis (cough with phlegm) among school children exposed to second-hand smoke (SHS) in cars, using a modified Irish International Study of Asthma and Allergies in Childhood (ISAAC) protocol.2,809 children of 13-14 yrs old and who selected randomly from post-primary schools throughout Ireland completed the 2007 ISAAC self-administered questionnaire. Adjusted OR (adjusted for sex, active smoking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 19 publications
3
41
0
2
Order By: Relevance
“…However, independent from this fact, we found significant correlations between smoking habits and measured particle concentrations. It has already been shown by earlier studies that indoor smoking increased risks for bronchitis and other respiratory diseases [3,4,10,11]. Our study may point to the fact that in particular particle exposure resulting from smoking contributes to bronchitis in children and not only gaseous components of ETS.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…However, independent from this fact, we found significant correlations between smoking habits and measured particle concentrations. It has already been shown by earlier studies that indoor smoking increased risks for bronchitis and other respiratory diseases [3,4,10,11]. Our study may point to the fact that in particular particle exposure resulting from smoking contributes to bronchitis in children and not only gaseous components of ETS.…”
Section: Resultssupporting
confidence: 68%
“…There are many indications that indoor smoking can increase risks for bronchitis, and other respiratory outcomes [3,4]. Heating and cooking may also be important indoor particle sources.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from increasing the cumulative lifetime exposure to tobacco smoke, the results of this study indicate that passive smoke exposure in childhood, in particular parental smoking, influence smoking habits in adulthood by increasing the likelihood of ever smoking and the total pack year cigarette consumption. Further efforts to reduce passive smoke exposure in automobiles are welcome initiatives that are undergoing legislative implementation in some countries at present (26).…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence that second-hand tobacco smoke exposure causes asthma, more severe asthma symptoms, bronchial hyperresponsiveness, airways inflammation and adverse effects on respiratory health in children and adolescents [64][65][66][67]. Studies in emergency departments have identified that children presenting with wheeze are more likely to be exposed to second-hand tobacco smoke compared with those presenting with other conditions and that second-hand tobacco smoke exposure is weakly associated with more severe acute asthma [66,68].…”
Section: Tobacco Smokementioning
confidence: 99%